“Fuimos todas”. Activismos feministas universitarios y comunidades emocionales: las tomas en la UNAM - Heredia Hernández, Rocío; Curiel, Charlynne (El Colegio de México A.C., 2025)
This paper explores the organized practices of the feminist activism and the emergence of “emotional communities” in the university context. Drawing on qualitative fieldwork conducted between 2019 and 2020 during the takeover of some of the departments of the National Autonomous University of Mexico (UNAM) by feminist collectives, we look at what happens e “backstage” in the practice of this activism. We explore how feminists not only used organizational methods to sustain the occupation of the unam but also generated spaces in which they could share the experiences of gender-based violence that triggered their activism in the first place. Overcoming a sense of victimhood, the students engaged in political actions to pressure the authorities, from a perspective that acknowledged the pain of others. This approached allowed them to critique of the institutional and sexist violence they experience. This article contributes to the growing field of studies on university feminist activism in dialogue with studies on emotions in socio-cultural analysis. It also presents an ethnographic account of practices that are less visible and powerful than what it is commonly understood as feminist action and mobilization.